Cell Death via Lipid Peroxidation and Protein Aggregation Diseases - Katsuya Iuchi; Tomoka Takai; Hisashi Hisatomi (Biology, 2021)
Lipid peroxidation of cellular membranes is a complicated cellular event, and it is both the cause and result of various diseases, such as ischemia-reperfusion injury, neurodegenerative diseases, and atherosclerosis. Lipid peroxidation causes non-apoptotic cell death, which is associated with cell fate determination: survival or cell death. During the radical chain reaction of lipid peroxidation, various oxidized lipid products accumulate in cells, followed by organelle dysfunction and the induction of non-apoptotic cell death. Highly reactive oxidized products from unsaturated fatty acids are detected under pathological conditions. Pathological protein aggregation is the general cause of these diseases. The cellular response to misfolded proteins is well-known as the unfolded protein response (UPR) and it is partially concomitant with the response to lipid peroxidation. Moreover, the association between protein aggregation and non-apoptotic cell death by lipid peroxidation is attracting attention. The link between lipid peroxidation and protein aggregation is a matter of concern in biomedical fields. Here, we focus on lethal protein aggregation in non-apoptotic cell death via lipid peroxidation. We reviewed the roles of protein aggregation in the initiation and execution of non-apoptotic cell death. We also considered the relationship between protein aggregation and oxidized lipid production. We provide an overview of non-apoptotic cell death with a focus on lipid peroxidation for therapeutic targeting during protein aggregation diseases.